The efficacy of Clove oil as an alternative ‎anaesthetic on common Carp (Cyprinus ‎carpio, L.)‎ (Journal of Hama University, 2022)
Clove oil is a natural anaesthetic that can help to calm stressed fish throughout both ‎‎‎‎biological and therapeutic processes such as artificial spawning. No mortality was ‎‎recorded among the fish subject to the tests specified in this research whether in the ‎‎anaesthesia or recovery phase. The reactions of common Carp were recorded for the ‎anaesthesia period with four ‎phases and for the recovery period with three phases where ‎no effects were observed for ‎the concentrations (5, 10 and 20 ppm) in anaesthetizing ‎fingerlings or adult individuals ‎while concentrations (60, 80, 100 and 120 ppm) ‎succeeded in anaesthetizing fingerlings‎, In addition to a concentration of 40 ppm in ‎anaesthetizing adult individuals. The ‎anaesthesia time for fingerlings ranged from 1.04 ‎minutes at a concentration of 60 ppm ‎for 2.28 minutes at a concentration of 120 ppm. ‎ The recovery time ranged from 4.44 minutes at a concentration of 80 ppm for 11.45 ‎‎minutes at a concentration of 120 ppm, While anaesthesia for adult individuals ranged ‎from 1.03 minutes at a concentration of ‎‎40 ppm for 1.45 minutes at a concentration of ‎‎120 ppm with recovery periods ranging ‎from 4.21 minutes at a concentration of 40 ppm ‎for 10.18 minutes at a concentration of ‎‎120 ppm.‎ The concentration of 80 ppm proved to ‎be better than the rest of the previous ‎concentrations (60, 100 and 120 ppm) for use in ‎anaesthetizing both fingerlings and ‎adult individuals together (P>0.05).‎